On Local Stability Loss of Modified Composites with Whiskerized Fibers - G. I. Kriven; D. S. Shavelkin (Учёные записки Казанского университета: Серия Физико-математические науки, 2024)
This article examines the critical compressive stresses required for a modified fiber composite to remain straight while the fibers within it bend. It was assumed that the modified composite consists of three phases: fiber, whiskerized interfacial layer, and matrix. An example of a composite material made up of carbon fibers, a whiskerized layer of carbon nanotubes with an epoxy matrix, and an epoxy matrix was considered. Its physical parameters affecting the critical compressive stresses were assessed, and methods for determining them were proposed. The effective properties of the inclusion and binder composite material were identified using the Voigt and Reis methods. Similarly, the effective properties of the interfacial whiskerized layer were analyzed by the three-phase method. The influence of fiber wavelength and phase shift, which define the destruction of the composite material, on the critical compressive stress value was explored. The wavelengths at which the composite material is destroyed were found. The effect of the volume content of the modified inclusion on the minimum critical compressive stress value was shown. The results for the modified composites were compared with those for the classical composites with a similar volume content of inclusions.